Pengolahan Tamagiri Nasi Uduk Buah Naga pada Resto Kebun Naga Poernama Garut - Neni Dewi Ratnaeni; Yosa Aulia (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
The purpose of this innovation is to add to the menu at Resto kebun Naga Poernama. Data collection was carried out by organoleptic tests on 25 people conducted by lecturers, industry and consumers. Based on the tabulation of organoleptic test data, the author can conclude that the Dragon Fruit Uduk Rice at Resto Kebun Naga Poernama. from the results of the calculation on the level of liking obtained the value in the main test as follows: appearance 80% (very like), 20% (like). Color 68% (very like), 32% (like). Aroma 44% (very like). 56% (like). Texture 76% (like), 24% (like). Taste 84% (like very much), 16% (like). Taste 80% (really like), 20% (like). so it is stated that Tamagiri Dragon Fruit Shrimp Rice is liked and acceptable by panelists. After obtaining the results of the Break Event Point calculation, it is concluded that for 1 portion of Tamagiri Dragon Fruit Shrimp Rice, it is Rp.6,075, while the selling price per portion is Rp.16,000 with a food cost of 37%, BEP of 166 pcs, fixed cost of Rp. 1,500,000 and it is concluded that in order to get a target margin of Rp. 2,000,000,- / month, it must sell as many as 388 pcs / month or 13pcs / day. The author's suggestion for future researchers is to make eggshells that are not fishy and add more varied fillings.